Conditions That Shape the Learning Curve: Factors That Increase the Ability and Opportunity to Learn - Wiersma, Eelke (Management Science, 2007)
Prior studies examining factors that influence the learning curve mainly focus on settings in which firms adopt new products or technologies or open new plants or assembly lines. Less is known, however, about how more mature firms learn, when they are further down the learning curve. To gain insight into factors that enhance learning in this situation, I examine factors that increase both the ability and the opportunity to learn. I hypothesize that the ability to learn is enhanced by the presence of a moderate amount of temporary employees in the workforce and by providing employees with related variation in tasks, measured by product heterogeneity. In addition, I hypothesize that opportunities for learning are created when there is some slack in resources and when there are no problems in other important performance dimensions that consume employee attention. These hypotheses are examined using data of the Royal Dutch Mail, which has 27 geographically dispersed regions. Although these 27 regions are homogeneous with respect to their tasks, internal organization, type of products delivered, and technology used, their learning rates differ considerably. In the sample of 972 observations used for this analysis, I find that this variation in learning rates is explained by the percentage of temporary employees used, the level of excess capacity, the degree of product heterogeneity, and the degree to which regions face problems in other important performance dimensions. These findings provide insight into strategies that help managers in designing work processes to maintain a positive learning curve.